Satellite tagging highlights the importance of productive Mozambican coastal waters to the ecology and conservation of whale sharks - Rohner,Christoph A; Richardson,Anthony J; Jaine,Fabrice R A; Bennett,Michael B; Weeks,Scarla J; Cliff,Geremy; Robinson,David P; Pierce,Simon J (PeerJ Preprints, 2017)
Recent advances in tracking technologies and analytical approaches allow for deeper insights into the movement ecology of wide-ranging fishes. The whale shark Rhincodon typus is an endangered, highly migratory species with a wide, albeit patchy, distribution through tropical oceans. Aerial surveys along the southern Mozambican coast, conducted over a 5-year period, documented the highest densities of whale sharks to occur within a ~200 km long stretch of the Inhambane Province, with a pronounced hotspot adjacent to Praia do Tofo. We tagged 15 juvenile whale sharks with SPOT5 satellite tags off Praia do Tofo and tracked them for 1–87 days (mean = 26 days) as they dispersed from this area. Sharks travelled between 10 and 2,737 km (mean = 738 km) at a mean horizontal speed of 29 ± 30.7 SD km day-1. While several individuals left shelf waters and travelled across international boundaries, most sharks stayed in Mozambican coastal waters over the tracking period. We tested for whale shark habitat preferences, using sea surface temperature, chlorophyll-a concentration and water depth as variables, by computing 100 random model tracks for each real shark based on their empirical movement characteristics. Whale sharks spent significantly more time in cooler, shallower water with higher chlorophyll-a concentrations than model sharks, suggesting that feeding in productive coastal waters is an important driver of their movements. Our results show that, while whale sharks are capable of long-distance oceanic movements, they can spend a disproportionate amount of time in specific areas. The increasing use of large-mesh gill nets in this coastal hotspot for whale sharks is a clear threat to regional populations of this iconic species.
Keywords: Rhincodon typus; Biotelemetry; Movement Ecology; Oceanography; Fishing Pressure